Effect Of Fermented Rice Straw With Ecoenzymes On Digestibility of Dry Matter and Organic Matter In Local Sheep - S. Umar; N. Ginting; Ginting, Yogi Rosalina (Jurnal Peternakan Integratif, 2022)
Rice straw with abundant availability becomes very potential to be used as local sheep feed. Fermentation needs to be done to improve the nutritional quality of rice straw which is quite low. The nutritional content needs to be considered in order to support the productivity of sheep. Local sheep is one of the livestock commodities that provide meat. This study aimed to determine the digestibility of dry matter and organic matter feed based on rice straw (oryza sativa) fermented with ecoenzymes in male local sheep. The research was carried out in Namorambe, Deli Serdang Regency, North Sumatra from January to March 2021 and at the Chemistry Postgraduate Laboratory, University of North Sumatra. The design used was a completely randomized design (CRD) with 5 treatments and 4 replications. The treatments consisted of P0 (100% odot grass without fermented rice straw), P1 (75% odot grass and 25% fermented rice straw), P2 (50% odot grass and 50% fermented rice straw), P3 (25% odot grass and 75% fermented rice straw), P4 (100% fermented rice straw without odot grass). The parameters observed were dry matter digestibility and organic matter digestibility. The results showed that the administration of fermented rice straw with ecoenzymes did not significantly affect the dry matter and organic matter digestibility of male local sheep. The conclusion of the study showed that the administration of fermented rice straw with ecoenzymes had the same dry matter and organic matter digestibility as odot grass.